Implementation of By Law of Town Palu of Number 3 Year 2016 About Garbage Management - Budiman Budiman; Mohamad Andri; Feriyal Umar Alhadad (Universitas Muhammadiyah Palu, 2020)
Palu Town still deal with the garbage problem which frequently become the society focus. Existence of garbage of around society can endanger the health and environmental if is not managed better. Garbage management intended by garbage to do not endanger the health and do not contaminate the environment and also to obtain;get the benefit for society prosperity. This research aim to to know its implementation is by law of Town of Number Palu 3 Year 2016 about Garbage Management. Research Type used by is deksriptif with the approach qualitative, doing/conducting perception, circumstantial interview ( indept interview) and documentation. Researcher Use The Theory of Policy Implementation of According To Mazmanian And Sabatier.Hasil Research show this Perda not yet walked optimal, Lack of Society Awareness in Managing Area Garbage Self-Supportingly, Inexistence Work Is Of Equal Among/Between Party DLH of With The Institution- Other Institution Like Special Police From Satpol PP To the Straightening Of The Perda. Conclusion from this research is perda of garbage management not yet implementation, because lack of awareness of area organizer to manage the garbage self-supportingly, society tend to offish to participate in managing garbage, only rely on the just just hygiene worker, inexistence work is of equal among/between party On duty Environment ( DLH) with Set Of Police Pamongpraja ( Satpol PP) in the sanction perda enforcer. Not yet the existence of Governor Regulation ( New Pergub) arranging Minimum Service Standard applying (SPM) in management of garbage management, uncommitt his/its is incentive and disisentif in the perda.